ChemInform Abstract: Condensation‐Driven Assembly of Boron‐Containing Bis(Heteroaryl) Motifs Using a Linchpin Approach. Issue 13 (March 2016) - Adachi, Shinya; Liew, Sean K.; Lee, C. Frank; Lough, Alan; He, Zhi; Denis, Jeffrey D. St.; Poda, Gennady; Yudin, Andrei K.
Abstract: A strategy for the synthesis of novel boron‐containing bis(heteroaryl) systems is outlined.